2012
DOI: 10.1039/c1dt11566a
|View full text |Cite
|
Sign up to set email alerts
|

The unprecedented preparation of dinuclear zinc(ii) complexes from 4-halido-2-[(3-cyclohexylaminopropylimino)methyl]phenol

Abstract: Three new centrosymmetric trinuclear nickel(II) and manganese(II) complexes, Ni[Ni(CH(3)COO)(CPA)](2) (1), Ni[Ni(CH(3)COO)(BPA)](2) (2), Mn[Mn(CH(3)COO)(BPA)](2) (3), where H(2)CPA = N,N'-bis(5-chlorosalicylidene)-1,3-propanediamine, H(2)BPA = N,N'-bis(5-bromosalicylidene)-1,3-propanediamine, and two new centrosymmetric dinuclear zinc(II) complexes, [Zn(2)(CMP)(2)] (4) and [Zn(2)(BMP)(2)] (5), where H(2)CMP = 4-chloro-2-{[3-(5-chloro-2-hydroxybenzyl)aminopropylimino]methyl}phenol, and H(2)BMP = 4-bromo-2-{[3-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The Zn atom deviates from the least squares plane defined by the equatorial donor atoms by 0.100(2) Å. The coordinate bond lengths in the com plex are comparable to those reported in similar zinc(II) complexes [9,10] In the IR spectrum of [Zn 2 L 2 ], there exists a char acteristic N-H vibration at 3225 cm -1 . The strong ab sorption band at 1629 cm -1 can be attributed to the vi bration of the azomethine groups, ν(C=N).…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…The Zn atom deviates from the least squares plane defined by the equatorial donor atoms by 0.100(2) Å. The coordinate bond lengths in the com plex are comparable to those reported in similar zinc(II) complexes [9,10] In the IR spectrum of [Zn 2 L 2 ], there exists a char acteristic N-H vibration at 3225 cm -1 . The strong ab sorption band at 1629 cm -1 can be attributed to the vi bration of the azomethine groups, ν(C=N).…”
Section: Introductionsupporting
confidence: 75%
“…It was found that the mono Schiff base ligand 4 chloro 2 [(3 cyclohexylami nopropylimino)methyl]phenol can be transformed to bis Schiff base ligand N,N' bis(5 chlorosalicylidene) 1,3 propanediamine under solvolthermal condition [8]. Then, they reported three interesting dinuclear zinc(II) complexes derived from mono Schiff bases bearing 2 [3 cyclohexylaminopropylimino]methyl]phe nol backbone under solvolthermal conditions [9,10]. It is interesting that the mono Schiff bases underwent structural transformation during the reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 And also an acetate and phenolate bridged trinuclear nickel complex was prepared by nickel acetate with H 2 L under solvothermal condition. 16 Interestingly, the present complex was prepared by the reaction of the Schiff base ligand with nickel acetate in a 2:3 molar ratio under ambient condition. Crystals of the complex are stable in air at room temperature, soluble in DMF, DMSO, MeOH, EtOH and MeCN, insoluble in water.…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, the halide and pseudohalide groups can link two or more metal atoms, yielding various polynuclear complexes. [4][5][6][7][8][9] To our knowledge, there are no bromido-bridged dinuclear copper complexes with Schiff bases derived from salicylaldehyde and its derivatives have been reported so far. In this study, a novel dinuclear Schiff base copper(II) complex with bromide and azide bridges, [Cu 2 Br 2 L 2 ]·[Cu 2 Br(N 3 )L 2 ]·H 2 O, where L is the deprotonated form of the Schiff base 4-chloro-2-[(2-hydroxyethylimino)methyl]phenol (HL; Scheme 1), was successfully prepared and characterized.…”
mentioning
confidence: 99%